Pengembangan Modul Fisika Berbasis CLIS untuk Meningkatkan Pemahaman Konsep dan Literasi Sains Siswa SMA - Dwi Irawati; Sulistiyono Sulistiyono (Departement of Mathematics Education, 2024)
This study aims to (1) Produce a CLIS-based physics module that is feasible to improve concept understanding and science literacy of high school students, (2) Know the improvement of students' concept understanding after using CLIS-based physics modules, (3) Know the improvement of students' science literacy after using CLIS-based physics modules. The method used in this research is a type of research and development (R&D). The development was carried out by referring to the ADDIE model with the stages of Analysis, Design, Development, Implementation, and Evaluation. The results showed that (1) CLIS-based physics modules are feasible to improve concept understanding and science literacy of high school students with the results of material expert validation of 55, media experts 56 and linguists 42 with very good categories; (2) an increase in student concept understanding of 0.70 with a high category and (3) an increase in student science literacy of 0.55 with a moderate category.